Harmonic Maps and Critical Points of Penalized Energy (Journal of Partial Differential Equations, 2003)
" We discuss a sequence solutions u_\u03b5 for the E-L equations of the penalized energy defined by Chen-Struwe. We show that the blow-up set of u_\u03b5 is a H^{m-2} - rectifiable set and its weak limit satisfies a blow-up formula. Consequently, the weak limit will be a stationary harmonic map if and only if the blow-up set is stationary."
Keywords: Harmonic map; blow-up formula; penalized energy